Multi-omics insights into the positive role of strigolactone perception in barley drought response - Daszkowska-Golec, Agata; Mehta, Devang; Uhrig, R Glen; Brąszewska, Agnieszka; Novak, Ondrej; Fontana, Irene M; Melzer, Michael; Płociniczak, Tomasz; Marzec, Marek (BMC plant biology, 2023)
BACKGROUND: Drought is a major environmental stress that affects crop productivity worldwide. Although previous research demonstrated links between strigolactones (SLs) and drought, here we used barley (Hordeum vulgare) SL-insensitive mutant hvd14 (dwarf14) to scrutinize the SL-dependent mechanisms associated with water deficit response. RESULTS: We have employed a combination of transcriptomics, proteomics, phytohormonomics analyses, and physiological data to unravel differences between wild-type and hvd14 plants under drought. Our research revealed that drought sensitivity of hvd14 is related to weaker induction of abscisic acid-responsive genes/proteins, lower jasmonic acid content, higher reactive oxygen species content, and lower wax biosynthetic and deposition mechanisms than wild-type plants. In addition, we identified a set of transcription factors (TFs) that are exclusively drought-induced in the wild-type barley. CONCLUSIONS: Critically, we resolved a comprehensive series of interactions between the drought-induced barley transcriptome and proteome responses, allowing us to understand the profound effects of SLs in alleviating water-limiting conditions. Several new avenues have opened for developing barley more resilient to drought through the information provided. Moreover, our study contributes to a better understanding of the complex interplay between genes, proteins, and hormones in response to drought, and underscores the importance of a multidisciplinary approach to studying plant stress response mechanisms.
Keywords: Hordeum; Perception; Droughts; multiomika; Strigolactone; Transcriptome; Multiomics; Abscisic acid; percepce; Drought; Phytohormone; ječmen (rod); Proteome; Barley (Hordeum vulgare); období sucha